How many men who have sex with men and female sex workers live in El Salvador? Using respondent-driven sampling and capture–recapture to estimate population sizes. Issue 4 (8th March 2011) - Paz-Bailey, G; Jacobson, J O; Guardado, M E; Hernandez, F M; Nieto, A I; Estrada, M; Creswell, J
Abstract : Objective: To estimate the numbers of female sex workers (FSW) and men who have sex with men (MSM) in San Salvador, El Salvador. Design and methods: A capture–recapture exercise was conducted among MSM and FSW in San Salvador in 2008. The first capture was done by distributing key chains to both MSM and FSW populations through local non-governmental organizations (NGO) that work with these groups. The second capture was done during the course of an integrated behavioural and biological survey (IBBS) using respondent-driven sampling (RDS). The proportion receiving a key chain estimated from the IBBS study was adjusted by RDS-derived weights. Results: The first capture included 400 FSW and 400 MSM. Of the 624 MSM interviewed in the IBBS, 36 (5.8% crude; 3.2% adjusted RDS) had received the key chain. The estimated population size of MSM in San Salvador was 12 480 (95% CI 7235 to 17 725). Of the 663 FSW interviewed in the IBBS, 39 (5.9% crude; 6.9% adjusted RDS) had received the key chain. The estimated number of FSW was 5765 (95% CI 4253 to 7277). Conclusions: The capture–recapture exercise was successfully linked to an IBBS to obtain city-level population sizes for MSM and FSW, providing valuable information at a low cost. Size estimates are crucial for programme planning for national AIDS programmes, NGOs and stakeholders working with these populations and for HIV projection models.